The Impact of AI-based Blended Learning on Learning Achievement among Second-year Physics Students at the College of Education - Bannaga Taha Elzubair Hessen; Olash Abdalrheem Hewary; Nedal Guma Fileen (Al-Qalam Institute, 2026)
This study aimed to investigate the impact of AI-based blended learning on the learning achievement of second-year physics students at the College of Education. The researchers employed a quasi-experimental design, with the study population comprising second-year students in the physics department. A purposive sample of 40 students was selected and divided into two equivalent groups: an experimental group and a control group, each consisting of 20 students. The researchers used achievement tests as data-collection tools, and appropriate statistical methods were applied to analyze the data using the Statistical Package for the Social Sciences (SPSS). The study concluded with several findings, the most significant of which included the presence of statistically significant differences at the 0.05 significance level in the academic achievement of second-year students in mathematics, favouring the experimental group that was taught using an AI-based blended learning strategy. Based on these results, the researchers recommended establishing a blended-learning infrastructure by preparing human resources and equipping computer laboratories appropriately to implement the blended-learning strategy effectively. They also suggested adopting blended learning strategies in teaching science in schools and universities, and organizing workshops and training sessions for faculty members on AI-based blended learning.